The role of the European public opinion and political elites on relations between the European Union and the İslamic Republic of İran - Hamid, Chato Shaker (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Uluslararası İlişkiler Anabilim Dalı, 2016)
Bu çalışmada Avrupa ve İran arasındaki sorunların siyasi elitler ve avrupa kamouyundaki görüşleri incelenmiştir.
Avrupa Birliği ve İran İslam Cumhuriyeti arasında ilişkiler Avrupa kamuoyu ve siyasi elitlerin rolü
The influence of public opinions and the political elite on leaders and decision-makers within a country and in domestic affairs is obvious. However, with the advancement of technology and tools, their impact on issues of foreign policy and international relations has become highlighted. In this study, while investigating the problems and differences that exist between the EU and Iran in the international scene, it is attempted to identify the attitude of people and political elite towards Iran according to the measures taken by European Parliament against Iran and based on polls available. This study examines the active role of Europe's political elites and public opinion in shaping foreign policy and decision-making related to issues of international reserves. It has introduced their negative attitude towards the behavior of the Islamic Republic of Iran at the international level as an obstacle to the development of relations between Iran and Europe. Key words: public opinion, the political elite, the Islamic Republic of Iran, the European Union, European Parliament, polls, foreign policy, international relations, leaders and decision-making bodies.
Keywords: Uluslararası İlişkiler; International Relations